S117 Chronic obstructive pulmonary disease exacerbations – characterising the relationship between symptom severity and airway inflammation. (12th November 2019) - Halner, A; Brightling, C; Bafadhel, M
Abstract : Background: Exacerbations of COPD are heterogeneous, with respect to symptoms and inflammation. We investigate the relationship between patient symptom profiles and inflammatory profiles at exacerbation. Methods: Visual Analogue Scale (VAS)-based symptom data were collected at exacerbation along with inflammatory cell data from a previous study. 1 Spearman's rho for the correlation between VAS symptoms and airways inflammation was performed. Principal components analysis (PCA) and K-means cluster analysis were performed on selected symptom variables to identify patient subgroups based on symptoms. Results: VAS sputum production, VAS sputum purulence and VAS cough at exacerbation correlated with sputum CCL17 (rs = -0.39, -0.34 and -0.28 respectively) and sputum CCL13 (rs = -0.28, -0.27 and -0.28 respectively) at exacerbation. VAS sputum production and purulence correlated with sputum IL5 (rs = -0.30 and -0.29) and correlated with sputum% neutrophils (rs = +0.31 in both). VAS sputum purulence correlated with sputum IL1B, TNFα, TNFR1/R2 (rs = +0.30, +0.30, +0.31 and +0.29 respectively). Two principal components described most of the variation in the symptoms data. The highest loading for these components were VAS sputum production and dyspnoea. Two clusters based on VAS sputum production and VAS dyspnoea were identified (table 1). Cluster 1 was characterised by a trend to more neutrophilic inflammatory profile (e.g. higher sputum% neutrophil) and less eosinophilic inflammatory profile (e.g. lower sputum IL5) compared to cluster 2. Conclusions: Exacerbations of COPD patients fall into two symptom-based severity groups, those with more severe symptoms measured by VAS and more neutrophilic and less eosinophilic airways inflammation than exacerbations with less severe symptoms. VAS could be used to identify treatment algorithms for patients with an exacerbation of COPD. Future studies which capture a greater number of exacerbations are required to assess whether the findings of our analysis are reproducible. Reference: Bafadhel M, McKenna S, Terry S, et al . Acute exacerbations of chronic obstructive pulmonary disease: Identification of biologic clusters and their biomarkers. Am. J. Respir. Crit. Care Med 2011; 184: 662–671.